School Well Being Siswa Kota Jambi - Yun Nina Ekawati; Nofrans Eka Saputra (Jurnal Akademika Baiturrahim Jambi, 2021)
This study aims to describe the indicators of a school well-being program in Jambi City. This research was conducted with an open survey method (open ended questionnaire), the analysis was carried out by categorization, axial coding, percentage, and a description of each category. The sampling technique is random sampling. This study included 239 high school students in Jambi City as respondents. The results showed that the indicators of a school well-being consisted of school conditions (having), social relations (loving), school self-fulfillment (being), and health status had been achieved even though in each component there was still unsatisfactory achievement indicator status. The main priority in realizing the development of a school well-being program in Jambi City includes planning to prepare relaxing facilities according to student needs, the role of teachers, constructive collaboration between teachers and parents, and strengthening physical and psychological health services. The implementation of the welfare school program is the responsibility of schools and stakeholders so that it is necessary to prepare for strengthening policies in governance, long-term plans, sources of funds, implementation, and supervision from local, provincial, and even Ministry level agencies